Does the growth of mobile markets cause the demise of fixed networks? Evidence from the European Union - Anne-Kathrin Barth; Ulrich Heimeshoff (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
The increasing usage of mobile communication and the declining demand for fixed line telephony in Europe make the analysis of substitutional effects between fixed and mobile networks a key aspect for future telecommunication regulation. Using a unique dataset which contains information on all 27 European Union members from 2003 to 2009, we analyze substitutability between fixed and mobile telecommunications services in Europe by applying dynamic panel data techniques. We find strong empirical evidence for substitution from fixed to cellular networks throughout Europe. In addition, the article reveals resulting policy implications.
Keywords: 330; dynamic panel model; fixed-mobile substitution; telecommunication markets